The Toda and Painlevé Systems Associated with Semiclassical Matrix-Valued Orthogonal Polynomials of Laguerre Type - Cafasso, M.,; de la Iglesia, M.D. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
Consider the Laguerre polynomials and deform them by the introduction in the measure of an exponential singularity at zero. In [Chen Y., Its A., J. Approx. Theory 162 (2010), 270-297], the authors proved that this deformation can be described by systems of differential/difference equations for the corresponding recursion coefficients and that these equations, ultimately, are equivalent to the Painlevé III equation and its Bäcklund/Schlesinger transformations. Here, we prove that an analogue result holds for some kind of semiclassical matrix-valued orthogonal polynomials of Laguerre type.